Ibtikar Tiknulujiya Adz-Dzaka’ Al-Ishthina’iyy Fi Wajibati Ath-Thalabah Bi Al-Lughah Al-Arabiyah: ابتكار تكنولوجيا الذكاء الاصطناعي في واجبات الطلبة باللغة العربية - Rosyada, Amrina; Hermiwati; Hadziq, Muhammad Fadhil; Pelealu, Nanda Dzikrillah; Hasyb, Muh Thahilal Jahidul (Proceeding International Conference on Education, 2025)
The development of artificial intelligence (AI) technology innovation has had a significant impact on the process of completing academic assignments, particularly in Arabic language learning in higher education. This study aims to examine students' perceptions of the use of AI technology in completing Arabic language assignments, using Davis's (1989) Technology Acceptance Model (TAM) theoretical framework, which focuses on two main indicators: perceived usefulness and perceived ease of use. The research method used was a qualitative approach with a phenomenological design to explore students' experiences in depth. Data were obtained from nine purposively selected Master of Arabic Language Education students at Maulana Malik Ibrahim State Islamic University of Malang, then collected through in-depth interviews and analysed thematically. The results showed that students felt that AI technology innovation was very helpful in completing assignments, especially in accelerating information access, compiling academic papers, and increasing learning efficiency. However, students were also aware of challenges in the form of potential dependency and the risk of declining critical thinking skills. The conclusion of this study confirms that AI innovation has great potential as an effective support for academic assignments, with the note that its use needs to be directed wisely and supported by strengthening technological literacy.